The role of social class in academic university contexts: exploring students' academic self-concept, educational expectations, and achievement goals - Marini, Mara; Parisse, Chiara; Pagliaro, Stefano; Giovannelli, Ilaria; Pietroni, Davide; Livi, Stefano (Frontiers in Psychology, 2025)
IntroductionDespite international progress, socioeconomic inequalities continue to significantly impact young people's opportunities to realize their full potential and actively engage in society. Research has demonstrated that socioeconomic factors are critical risk factors for undergraduate students' adaptation and academic success. However, the psychological processes underlying this phenomenon remain inadequately understood.MethodsTo address this gap, we conducted two studies involving university students. Study 1 explored the relationship between socioeconomic status (both objective [parents' educational attainment] and subjective [subjective social status] indicators), students' academic self-concept, and educational expectations. In Study 2, we investigated the moderating role of achievement goals in the relationship between socioeconomic status and academic self-concept.ResultsThe findings indicated that socioeconomic barriers were negatively related to students' educational expectations through academic self-concept. Additionally, low performance-avoidance goals were found to enhance first-generation students' academic self-concept.DiscussionThese results underscore the importance of supporting students from low socioeconomic backgrounds, thereby improving their self-perceptions in academic settings and assisting them to achieve their educational goals.